Spatio-Temporal Analysis and Driving Factors of Soil Water Erosion in the Three-River Headwaters Region, China - Wu, Dan; Peng, Rui; Huang, Lin; Cao, Wei; Huhe, Taoli (Water (Basel), 2022)
Soil water erosion is considered to be a major threat to ecosystems and an important environmental problem. Aggravation of soil and water loss in the Three-River Headwaters Region (TRHR) is a prominent problem in China. In this research, the Revised Universal Soil Loss Equation (RUSLE) was applied to evaluate annual soil loss caused by water erosion in the TRHR from 2000 to 2020. Spatiotemporal patterns of soil water erosion were analyzed and the main driving factors of rainfall erodibility and vegetation coverage were investigated using ArcGIS spatial analysis. The results revealed that during the study period, soil erosion in the TRHR averaged 10.84 t/hm2/a, and values less than 25 t/hm2/a were characterized as micro and mild erosion. The soil erosion modulus observed a slightly increasing trend over the past decade. The changing trends in the Yangtze, Huanghe, and Lancang river source regions (YRSR, HRSR, and LRSR) were 0.03, 0.07, and 0.03 t/hm2/a, respectively. Both rainfall erodibility and vegetation coverage observed a growing trend, with slopes of 6.78 MJ·mm/(t·hm2·a) and 0.12%/a, respectively. In general, variation of rainfall erodibility showed a relatively higher contribution to soil erosion than vegetation coverage. Findings of this study could provide information for sustainable vegetation restoration, soil conservation, and water management at a regional scale.